A mortality prediction rule for non-elderly patients with community-acquired pneumonia. Issue 1 (December 2016) - Tashiro, Masato; Fushimi, Kiyohide; Takazono, Takahiro; Kurihara, Shintaro; Miyazaki, Taiga; Tsukamoto, Misuzu; Yanagihara, Katsunori; Mukae, Hiroshi; Tashiro, Takayoshi; Kohno, Shigeru; Izumikawa, Koichi
Abstract Background No mortality prediction rule is suited for non-elderly patients with community-acquired pneumonia. Therefore, we tried to create a mortality prediction rule that is simple and suitable for non-elderly patients with community-acquired pneumonia. Methods Because of low mortality at young age, we used information from an administrative database that included A-DROP data. We analysed the rate and risk factors for in-hospital community-acquired pneumonia-associated death among non-elderly patients and created a mortality prediction rule based on those risk factors. Results We examined 49, 370 hospitalisations for patients aged 18–64 years with community-acquired pneumonia. The 30-day fatality rate was 1.5 %. Using regression analysis, five risk factors were selected: patient requires help for feeding, the existence of malignancy, confusion, low blood pressure, and age 40–64 years. Each risk factor of our proposed mortality risk scoring system received one point. A total point score for each patient was obtained by summing the points. The negative likelihood ratio for the score 0 group was 0.01, and the positive likelihood ratio for the score ≥4 group was 19.9. The area under the curve of the risk score for non-elderly (0.86, 95 % confidence interval: 0.84–0.87) was higher than that of the A-DROP score (0.72, 95 % confidence interval: 0.70–0.74) (P  < 0.0001). Conclusions Our newly proposed mortality risk scoring system may be appropriate for predicting mortality in non-elderly patients with community-acquired pneumonia. It showed a possibility of a better prediction value than the A-DROP and is easy to use in various clinical settings.